2000
DOI: 10.1136/oem.57.9.635
|View full text |Cite
|
Sign up to set email alerts
|

Development of an asthma specific job exposure matrix and its application in the epidemiological study of genetics and environment in asthma (EGEA)

Abstract: Objectives-To develop a method suitable for estimating exposure risks in population studies of asthma from job titles and international codes, by combining a new job exposure matrix (JEM) with the expert judgement approach. The method was applied in the French epidemiological study of the genetics and environment in asthma (EGEA). Methods-The JEM contains 22 exposure groups including 18 high risk groups based on known risk factors for occupational asthma, divided into high molecular weight agents, low molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
200
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(208 citation statements)
references
References 22 publications
5
200
1
2
Order By: Relevance
“…In the present analysis we evaluated occupational exposure to specific asthmagens by an asthma-specific JEM combined with an expert review step [13,19]. Re-evaluation by an expert blinded to disease status ensured the objectiveness of the method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present analysis we evaluated occupational exposure to specific asthmagens by an asthma-specific JEM combined with an expert review step [13,19]. Re-evaluation by an expert blinded to disease status ensured the objectiveness of the method.…”
Section: Discussionmentioning
confidence: 99%
“…Re-evaluation by an expert blinded to disease status ensured the objectiveness of the method. To limit misclassification errors, specificity was favoured; a job was classified as exposed to asthmagen only if the probability of exposure was high for an important number of subjects in that job [19]. There is no evidence for recall bias in job history [22], but we are not aware of misclassification errors especially for 10-year exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational exposure can be estimated using a single-item question of exposure or by using a JEM based on job titles [14,36]. Some argue that a JEM leads to more accurate measures of occupational exposure, while others have reported that the difference between self-reporting and JEM are less than expected and that a question of VGDF-exposure is applicable in epidemiological research [1416].…”
Section: Discussionmentioning
confidence: 99%